POLITICS IN PUBLIC SERVICES OF TANGERANG CITY GOVERNMENT DOMESTIC WASTEWATER MANAGEMENT - Dafyar Eliadi (Universitas Padjadjaran, 2023)
Tangerang City is the most populous city in Banten Province, it has the potential to cause environmental problems. One of the problems in Tangerang City is the management of domestic wastewater. This study aims to analyze the politics in public services of Tangerang City Government for Domestic Wastewater Management. This study used a qualitative method with descriptive analysis, where the data sources consisted of primary and secondary data. Primary data were obtained from interviews and observations and secondary data was obtained from documents issued by the Tangerang City Government. The results of this study indicate that the Tangerang City Government has assigned several agencies, such as the Regional Planning Agency, the Health Office, and the Department of Housing, Settlement, and Land, to respond to political demands from the community in managing domestic wastewater. In public service politics, the Tangerang City Government not only provides facilities and formulates service management, but also makes democratic local regulations and opens up space for the community to provide input and evaluation. In addition, this study finds that local regulations do not regulate substantive issues as institutions that bind domestic wastewater management in Tangerang City. The Tangerang City Government realizes that meeting the needs of the community is a political responsibility that must be fulfilled.